The state of Pacific towns and cities urbanization in ADB's Pacific developing member countries. (Pacific studies series, 2012)
This report investigates urbanization trends across the 14 Pacific developing member countries of the Asian Development Bank. It examines the history of Pacific urbanization, current state of infrastructure and service provision within urban areas, and systems of urban governance.